2020
DOI: 10.3897/zookeys.915.47460
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis confirms the freshwater origin of the endemic Caspian sponges (Demospongiae, Spongillida, Metschnikowiidae)

Abstract: The Caspian Sea is a unique inland brackish waterbody inhabited by highly endemic fauna. This fauna consists of species of both marine and freshwater origin. Some Caspian invertebrates cannot be confidently referred to as animals of either origin. The endemic monophyletic family of sponges, Metschnikowiidae, is among them. Although these sponges are considered as fresh water in the modern literature, no researcher has seen them alive for many years, and its status is actually unconfirmed. Here, we present the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…It is noteworthy that samples of each species from geographically remote areas were included in the analysis. Also noteworthy is the fact of greater genetic divergence of Trochospongilla horida, which is also confirmed by the analysis of other genetic markers [9,11,16,21,22]. Therefore, sequence alignment and our phylogenetic analyses identified 28S rDNA as the suitable barcoding marker for Spongillidae.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…It is noteworthy that samples of each species from geographically remote areas were included in the analysis. Also noteworthy is the fact of greater genetic divergence of Trochospongilla horida, which is also confirmed by the analysis of other genetic markers [9,11,16,21,22]. Therefore, sequence alignment and our phylogenetic analyses identified 28S rDNA as the suitable barcoding marker for Spongillidae.…”
Section: Resultssupporting
confidence: 77%
“…For the Folmer fragment of the COX1 gene, there are a sufficient number of freshwater sponge sequences in the Genbank, but it has been shown that it is a conservative marker, and many sponge species have identical sequences [8,[18][19][20][21]. ITS1 and ITS2 spacers of rDNA have good resolution at the species and genus levels, but their use is difficult in the higher-level taxonomic groupings [9,11,16,21,22]. The ITS1 and ITS2 spacers worked well at the species level in Spongillidae because the species studied formed monophyletic clusters.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the ITS2 sequence, single sequences for the three species were obtained. Although several genotypes were found from the COI, there were a few cases in which a single sequence was found within the species in ITS2 (Jung et al 2018;Sokolova et al 2020). Zhou et al (2020) also reported that two genotypes in N. gallinarum were found in the COI although the sequences of ITS2 were identical within the species.…”
Section: Discussionmentioning
confidence: 98%
“…These spines can be extremely small and totally invisible under LM, as those in a C. ultima specimen described here (Figure 3), or hardly visible, as those in a specimen from Myanmar . Moreover, in Spongillida the number of spines often varies from spicule to spicule, for example, in E. fluviatilis (Manconi & Pronzato, 2002), and from sponge to sponge, for example, in Spongilla alba Carter, 1849 (our unpublished data) or Metschnikowia tuberculata Grimm, 1877 (Sokolova et al, 2020). Many spicules should be meticulously checked under SEM to be sure that none of the spines was missed.…”
Section: Note Onmentioning
confidence: 95%
“…For the dataset 1, 68 additional 28S haplotypes were collected from published sources using GenBank (Borchiellini et al, 2004;Erpenbeck et al, 2011;Gazave et al, 2010;Idan et al, 2018;Leal et al, 2016;Morrow et al, 2012Morrow et al, , 2019Nichols, 2005;Plotkin et al, 2017;Redmond et al, 2011;Thacker et al, 2013;Wiens et al, 2009;Zhou et al, 2019) (Table S1). In its turn, altogether 137 additional haplotype sequences were sampled from GenBank for the nuclear dataset 2 (Addis & Peterson, 2005;Bukshuk & Maikova, 2020;Itskovich et al, 2008Itskovich et al, , 2013Itskovich et al, , 2017Karlep et al, 2013;Maikova et al, 2010;Sokolova et al, 2020;Wiens et al, 2009) (Table S2).…”
Section: Ta B L Ementioning
confidence: 99%